Copper iodide mediated telescoped synthesis of 3-cyanoimidazo[1,2-a]pyridines, photophysical and DFT studies - Saha P.; Indurthi H.K.; Das S.; Diwan H.; Sharma D.K. (My University, 2025)
An efficient copper iodide-mediated synthesis of 3-cyanoimidazo[1,2-a]pyridines (4a-4m) from readily available methyl ketones, amino pyridines, and ethyl(ethoxymethylene)cyanoacetate is described. Copper(I)-catalyzed annulation between different aminopyridines and various methyl ketones resulted in the formation of imidazo[1,2-a]pyridines (IPs). The resulting IPs undergo C3 cyanation by cyanide anion generated from C(sp2)-CN bond cleavage of ethyl(ethoxymethylene)cyanoacetate. Mechanistic studies indicate that the cyanation of IP derivatives proceeds through a two-step sequence: initial iodination and then cyanation. The one-pot reaction has a wide substrate scope and high functional group tolerance and can be safely conducted on a gram scale. Further, we have studied the light-emitting properties of synthesized compounds. The absorption and emission spectra of compounds 4a and 4f were experimentally and computationally analyzed. Also, HOMO/LUMO distributions of compounds 4a and 4f were elucidated theoretically. © 2023 Elsevier B.V.